A física de colisões : uma abordagem de ensino-aprendizagem por meio do ambiente 3D Vpython - Paes, João Bosco Rodrigues (2016)
This paper aims to develop a strategy for the first grade of high school. Our project was developed in the city of Cáceres-MT located 200 km from Cuiabá in the State School “Frei Ambrosio” located in the peripheral area of the city. This project was developed through computer animation, and to do this we chose the so-called virtual platform “Visual Python”, or simply Vpython, that allows building animations of physical systems in 3D using the Python programming language. We create a set of animations relating to Physics one-dimensional and two-dimensional collisions, by which we work with students the principle of conservation of momentum as well as the different types of elastic and inelastic collisions, as well incorporating them into the teaching- learning process high school physics students. We conducted pre-tests preceding the effective implementation of the educational product that allowed us to identify some previous knowledge of students. The product performance is anchored in the Ausubel Theory of Meaningful Learning. We can see that results collected by the use of animations in Physics classes were quite satisfactory, especially as the motivation a key factor in the student learning, which lead us to believe that our project will contribute to the acquisition and understanding of the physical concepts involved, making them a suitable ally for the 21st century physics teaching physics.